1998
DOI: 10.1152/jn.1998.79.4.2171
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Contrast Enhancement via GABAC Feedback at Bipolar Terminals in the Tiger Salamander Retina

Abstract: Most retinal amacrine (ACs) and ganglion cells (GCs) express temporal contrast by generating action potentials at only the onset and offset of the light stimulus. This study investigated the neural mechanisms that underlie this temporal contrast enhancement. Whole cell patch recordings were made from bipolar cells (BCs), ACs, and GCs in the retinal slice preparation. The cells were identified by the locations of their somas in the inner nuclear layer and ganglion cell layers, their characteristic light respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(156 citation statements)
references
References 41 publications
13
140
3
Order By: Relevance
“…Similar changes in the amplitude and kinetics of glycinergic responses by GABA antagonists in light-adapted preparations were attributed to blocking GABA A receptors on glycinergic amacrine cells (Zhang et al, 1997;Roska et al, 1998). Blocking GABA C receptors on bipolar terminals, which increases excitatory input from bipolar cells to third-order neurons Dong and Werblin, 1998), could also cause a rapid increase in glycinergic IPSCs. The fact that picrotoxin never caused a rapid enhancement of glycinergic IPSCs in dark-adapted retinas supports the idea that in dark-adapted retinas the glycinergic amacrine cells are suppressed by a separate action of GABA.…”
Section: What Causes the Rapid Enhancement Of Glycinergic Ipscs By Pimentioning
confidence: 84%
See 1 more Smart Citation
“…Similar changes in the amplitude and kinetics of glycinergic responses by GABA antagonists in light-adapted preparations were attributed to blocking GABA A receptors on glycinergic amacrine cells (Zhang et al, 1997;Roska et al, 1998). Blocking GABA C receptors on bipolar terminals, which increases excitatory input from bipolar cells to third-order neurons Dong and Werblin, 1998), could also cause a rapid increase in glycinergic IPSCs. The fact that picrotoxin never caused a rapid enhancement of glycinergic IPSCs in dark-adapted retinas supports the idea that in dark-adapted retinas the glycinergic amacrine cells are suppressed by a separate action of GABA.…”
Section: What Causes the Rapid Enhancement Of Glycinergic Ipscs By Pimentioning
confidence: 84%
“…The immediate block of ganglion cell responses to GABA puffs indicates that GABA A receptors were rapidly blocked. Because GABAergic feedback to bipolar cell terminals in salamander retina is mediated mainly by GABA C receptors (L ukasiewicz et al, 1994;Dong and Werblin, 1998) the rapid enhancement of EPSC s indicates that GABA C receptors were also rapidly blocked. Other studies have also shown that GABA C receptors are rapidly blocked by picrotoxin (C. R. Shields and P. D. Lukasiewicz, unpublished observations) (see also Feigenspan and Bormann, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lateral inhibition in the IPL, which contributes to the surround of ganglion cells, is mediated by GABA (Cook and McReynolds, 1998;Flores-Herr et al, 2001). In addition, GABAergic inhibition in the IPL also may shape the temporal responses of ganglion cells (Dong and Werblin, 1998) and is a key player in the signaling that determines their motion and direction sensitivity (Caldwell et al, 1978).…”
Section: Ganglion Cell Layer and Inner Nuclear Layermentioning
confidence: 99%
“…The GABA receptors, which mediate these two types of inhibition, are different. IPSCs in ganglion cells are mediated by GABA A receptors, whereas IPSCs in bipolar cells are mediated mainly by GABA C receptors (Dong and Werblin 1998;Ichinose and Lukasiewicz 2002;Lukasiewicz and Shields 1998). In addition, the amacrine cell types that contact bipolar and ganglion cells may be different.…”
Section: Kainate Puff-evoked Gabaergic Ipscs In Ganglion Cells Dependmentioning
confidence: 99%